PENGARUH DUKUNGAN MANAJEMEN PUNCAK, KECANGGIHAN TEKNOLOGI INFORMASI, DAN PELATIHAN TERHADAP KINERJA SISTEM INFORMASI AKUNTANSI - Satika Zahra Amalia (2024)
This research aims to examine the effect of top management support, information technology sophistication, and training influence the performance of accounting information systems. The population of this study are accounting information system users who work in manufacturing and construction companies whose operational offices are located in DKI Jakarta, Bogor, Bekasi and Depok. This research used the Cluster Sampling technique and obtained 83 respondents. This type of research is quantitative using primary data. This research data was analyzed using the multiple linear regression method with a significance of 5% or 0.05. The results of this research are that top management support and the sophistication of information technology influence the performance of accounting information systems. Meanwhile, training has no effect on the performance of the accounting information system.